2007
DOI: 10.1021/jf0717485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seasonal Changes on Content and Profile of Soluble Carbohydrates in Tubers of Different Varieties of Jerusalem Artichoke (Helianthus tuberosus L.)

Abstract: A high content (60-65% of dry mass DM) of water soluble carbohydrates was found in early harvested varieties (Bella and Bianka) and middle early varieties (Topstar and Gigant) harvested 22-25 weeks after plantation. In late varieties (Waldspindel, Violet de Rennes, Rote Zonenkugel) a similar amount was obtained (55-60% of DM) when harvested 29-33 weeks after planting. There was a distinctive impact on maturing process as well as frost period alterations which resulted in conversion of high polymer inulin to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 28 publications
3
46
1
Order By: Relevance
“…The differences in the reported values may be due to the analytical method used, the variation in climatic conditions, soil conditions, maturity levels and varieties of the particular plant (Carvalho et al, 1998;Kociss et al, 2007;Vandoorne et al, 2012). Loo et al (1995) reported Taraxacum officinale FW).…”
Section: Scientific Namementioning
confidence: 99%
“…The differences in the reported values may be due to the analytical method used, the variation in climatic conditions, soil conditions, maturity levels and varieties of the particular plant (Carvalho et al, 1998;Kociss et al, 2007;Vandoorne et al, 2012). Loo et al (1995) reported Taraxacum officinale FW).…”
Section: Scientific Namementioning
confidence: 99%
“…Twenty percent of inulin chains are with DP>10 (Kays and Nottingham, 2007) and over 44% of inulin from Helianthus tuberosus L has DP >13 (Hempel et al, 2007). The most common is the fraction with DP 12-16 (Kocsis et al, 2007). Inulin in Jerusalem artichoke tubers ranges up to above (DP 40) (Kays and Nottingham, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The content of DF comprising soluble carbohydrates in Jerusalem artichoke tubers has previously been investigated in unpeeled tubers and was found to depend on harvest time, variety and postharvest conditions [Kocsis et al 2007, Slimestad et al 2010.…”
Section: Resultsmentioning
confidence: 99%
“…The content of WSC in the developing tubers is generally high; however, the variation in WSC is mainly based on the genetic predisposition of different varieties [Kocsis et al 2007;Liu et al 2015]. By Liu et al [2015] soluble sugar content of Jerusalem artichoke tuber in different genotypes have been varied between 30.7 and 68.0%.…”
Section: Resultsmentioning
confidence: 99%